Odontopediatrics integral treatment in cerebral paralysis. - Nima Bermejo, Gabriel (2005)
Report a case of girl of 4 years 3 months with congenital cerebral palsy distonic caused by citomegalovirus infectión with convulsive sindrome. The patient was referred to the pediatric dentistry departament at the dental school of the Universidad Nacional Mayor de San Marcos (UNMSM) for her odontopediatric treatment. The patient had an integral evaluation and treatment with no conventional dental procedures, without consciencious sedation. Having in consideration her age and cooperation level. Several medical and dental specialities was included. A significative diminishment in the convulsive frecuency after the dental treatment was referreal. Finally the of importance integrate odontology into multisciplinary team that works with this kind of patient is remarked.